Pauls as critic: The form, ethics, and uses of an ananachronistic reader - Rodríguez Montiel, Emiliano (Revista Chilena de Literatura, 2022)
The aim of this paper is to explore and to analyze the critical production by Alan Pauls. Specifically, the form, ethics and literary uses he develops he comments and analyzes the work of others. The hypothesis is guided by a series of questions –How does he read, when he reads others? What vocabulary, resources, and figures of speech make up his critical writing? What principle, truths, and persistences shape his ethics as a critical reader? What does he expropriate, what does he keep when intruding in others‘ fiction? –, my hypothesis is that such critical production a) evaluates books according to an economic vocabulary and logic; b) practices a cult of the untimely according to an affirmative conception and use of anachronism; and c) exhibits the principles and operations that his literature extracts from a national anti-historicist library: Borges, Saer, Puig y Piglia.